Unraveling Genetic Causality Between Type 2 Diabetes Mellitus and Hemiplegia Based on Mendelian Randomization - Li Y; Zhang Z; Jin W; Yuan Y; Cen X; Tan J; Wu X (Journal of Multidisciplinary Healthcare)
Ying Li,1,* Zhengyu Zhang,2,* Wen Jin,2 Yuan Yuan,3 Xingzu Cen,2 Juntao Tan,4 Xiaoxin Wu5 1Department of Medical Administration, the First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, 310003, People’s Republic of China; 2Medical Records Department, the First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, 310003, People’s Republic of China; 3Medical Records Department, Women and Children’s Hospital of Chongqing Medical University, Chongqing, 401147, People’s Republic of China; 4College of Medical Informatics, Chongqing Medical University, Chongqing, 400016, People’s Republic of China; 5State Key Laboratory for Diagnosis and Treatment of Infectious Diseases, National Clinical Research Centre for Infectious Diseases, the First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang, 310003, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaoxin Wu, State Key Laboratory for Diagnosis and Treatment of Infectious Diseases, National Clinical Research Centre for Infectious Diseases, the First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang, 310003, People’s Republic of China, Tel +8615988112032, Email xiaoxinwu@zju.edu.cn Juntao Tan, College of Medical Informatics, Chongqing Medical University, Chongqing, 400016, People’s Republic of China, Tel +8618375753171, Email tanjuntao@hospital.cqmu.edu.cnPurpose: Observational studies have shown a high comorbidity rate between type 2 diabetes mellitus (T2DM) and hemiplegia, but the causal relationship between the two remains to be proven. Therefore, we performed two-sample Mendelian randomization (MR) analysis to explore the causal relationship between T2DM and hemiplegia.Methods: Genome-wide association study (GWAS) data related to hemiplegia was obtained from the FinnGen study. We also obtained GWAS data for T2DM from the IEU OpenGWAS project. Single nucleotide polymorphisms (SNPs) that were closely associated with T2DM were selected as instrumental variables (IVs) (P < 5× 10− 8, r2 < 0.001). The causal effects were evaluated using inverse variance weighted (IVW), MR-Egger, weighted median, simple mode, and weighted mode. Subsequently, Cochran’s Q statistic was used to calculate the magnitude of heterogeneity and the MR-Egger method was used to detect level pleiotropy to ensure the reliability of the results. A leave-one-out sensitivity analysis was conducted to assess stability.Results: A total of 170 independent SNPs were selected as IVs to assess the genetic causality between T2DM and hemiplegia. Our findings suggest that genetic liability to T2DM has been linked with increased risk of hemiplegia (IVW: OR = 1.168, 95% confidence interval [CI], 1.025– 1.331, P = 0.020; weighted median: OR = 1.257, 95% CI = 1.023– 1.544, P = 0.030). Results of comprehensive sensitivity analysis were consistent with the main causality estimate. There was no significant heterogeneity or horizontal pleiotropy bias in this result.Conclusion: This study shows a causal relationship between T2DM and hemiplegia, indicating that T2DM increases the risk of hemiplegia, which may provide guidance for additional hemiplegia screening in T2DM patients.Keywords: type 2 diabetes mellitus, hemiplegia, Mendelian randomization, IEU OpenGWAS, genetic causality